One central bank to rule them all - Brusa, F; Savor, P; Wilson, M (Oxford University Press, 2019)
While global stock markets enjoy high returns on days surrounding FOMC meetings, there is no comparable result for other central banks either internationally or, more surprisingly, domestically. Neither announcement surprises nor currency moves drive these Öndings, which hold even for stocks with a domestic focus. The di§erence in announcement premia is not explained by economy size, exposure to multinationals, or policy activism. We conclude that the Fed exerts a unique impact on global equities. Consistent with this hypothesis, uncertainty drops across global markets following FOMC announcements but not those of other central banks. Furthermore, the Fed is generally the leader among central banks in setting monetary policy.